Effects of chromium and bismuth on secondary aluminium foundry alloys. (August 2013) - Timelli, G; Ferraro, S; Fabrizi, A
Abstract : The effects of impurities such as chromium and bismuth on the microstructure and mechanical properties of an AlSi9Cu3(Fe) secondary die casting alloy are investigated. Metallographic and image analysis techniques have been used to examine the microstructural changes. The results indicate that the area fraction and the size of brittle α -Alx (Fe, Mn, Cr)y Siz intermetallic compounds increase by increasing the Cr content, and this affects the ultimate tensile strength and the ductility of the alloy at higher Cr level. On the other hand, the Bi addition seems to not produce significant changes in the microstructure and in the average mechanical properties of the secondary AlSi9Cu3(Fe) alloy. However, the Weibull statistics show that the addition of Bi leads to less reliable castings, which may be associated with an increase in oxide film defects.